(untitled) (Sociologisk Forskning, 1994)
The family between market and state. A question of gender, class an power With reference to the far-reaching social and economic changes from a global perspective, the focus of the political discussions is now laid on the conditions of family life. The family is a third sphere between the market and the state. As such, it cannot be analysed independently of changes on the labour market and in the political economy. In this article, the thesis is advanced that the family policies must be analysed with reference to class and gender. The way in which changes in the composition of classes affect the current political process in Sweden is problematised. The significance of analysing the class relation of the service society from a gender perspective is particularly stressed. Sweden is currently a gender segregated class society. The higher classes are male dominated, and the lower classes are female dominated. A gender-based ’class struggle’ has emerged within strata. The solidarity within and between strata is weakened, since the struggle is also a gender struggle, and men tend to emphasise their higher status against women, not to equalise it. The bill about care allowance is critically scrutinised from class political and gender political perspectives. While presented as an issue of equality between family forms, it is argued, in this article, that its purpose is to strengthen a traditional family form in the working class.